Shin Evangelion : quand Anno Hideaki retourne (à) la Terre - Antonin Bechler; Kenjirō Muramatsu (Ebisu: Études Japonaises)
The Evangelion franchise, based on the animated series and films directed by Anno Hideaki, has held a significant place in the Japanese cultural ecosystem since 1995, particularly for its role in the development of the consumer culture known as “otaku”. This culture is characterized by its tendency to deliberately blend reality and virtuality, giving rise to phenomena such as “anime tourism”. Assuming that Evangelion reflects an evolution regarding the relationship with reality in contemporary Japan, this article focuses on its director’s background, the thematic and cinematic specificities of his works, with a focus on the final feature film of 2021 and its surprisingly in-depth depiction of a “rural community”. In doing so, the article questions the meanings and status of the “reality” depicted in the film.